PD-L1 Inhibits T Cell-Induced Cytokines and Hyaluronan Expression via the CD40-CD40L Pathway in Orbital Fibroblasts From Patients With Thyroid Associated Ophthalmopathy - Liu, Zhibin; Liu, Yao; Liu, Mingming; Gong, Qingjia; Shi, Anjie; Li, Xiuhong; Bai, Xu; Guan, Xiaoyue; Hao, Bing; Liu, Feila; Zhou, Xing; Yuan, Hongfeng (Frontiers in Immunology, 2022)
Thyroid associated ophthalmopathy (TAO), characterized by T cell infiltration and orbital fibroblast activation, is an organ-specific autoimmune disease which is still short of effective and safety therapeutic drugs. The PD-1/PD-L1 pathway has been reported hindering the progression of Graves’ disease to some extent by inhibiting T cell activity, and tumor therapy with a PD-1 inhibitor caused some adverse effects similar to the symptoms of TAO. These findings suggest that the PD-1/PD-L1 pathway may be associated with the pathogenesis of TAO. However, it remains unknown whether the PD-1/PD-L1 pathway is involved in orbital fibroblast activation. Here, we show that orbital fibroblasts from patients with TAO do not express PD-L1. Based on in vitro OF-T cell co-culture system, exogenous PD-L1 weakens T cell-induced orbital fibroblast activation by inhibiting T cell activity, resulting in reduced production of sICAM-1, IL-6, IL-8, and hyaluronan. Additionally, exogenous PD-L1 treatment also inhibits the expression of CD40 and the phosphorylation levels of MAPK and NF-κB pathways in orbital fibroblasts of the OF-T cell co-culture system. Knocking down CD40 with CD40 siRNA or down-regulating the phosphorylation levels of MAPK and NF-κB pathways with SB203580, PD98059, SP600125, and PDTC can both reduce the expression of these cytokines and hyaluronan. Our study demonstrates that the orbital immune tolerance deficiency caused by the lack of PD-L1 in orbital fibroblasts may be one of the causes for the active orbital inflammation in TAO patients, and the utilization of exogenous PD-L1 to reconstruct the orbital immune tolerance microenvironment may be a potential treatment strategy for TAO.